AdvancED actionScript 3.0 design patterns - Smith, Ben (Apress, 2011)
AdvancED ActionScript 3.0 is a fresh look and new approach to utilizing valuable, structural techniques and methods that are commonly used in the field of rich interactive application development. With each method broken down into different strategized explanations, you'll find the approach most suitable for you. Whether it is an example you can utilize as-is, or one you can start with and develop further, you will have a glossary of definitions and organizational concepts at your fingertips. Object-oriented programming (OOP) and design patterns are not new to the field, but can often be overlooked in their value. They are, at times, not only overwhelming to learn, but difficult to put into practice. However, they are useful because they create a structure that can be broken down, rebuilt, and reused.   Provides the building blocks required for the implementation of OOP Addresses problems and concerns regarding OOP Offers solutions on how to approach and utilize OOP